Digital Nature and Prophetic Ethics: A New Paradigm of IslamicEducation Philosophy for the Millennial Generation - Eni Latifah; Saniah (Educatia : Jurnal Pendidikan dan Agama Islam, 2026)
This study aims to analyze the concept of the millennial generation from the perspective of Islamic educational philosophy by reconstructing the concepts of fitrah (innate human nature) and moral character within the digital era. Rapid advancements in information technology have altered social values ​​and created new challenges for Islamic education in preserving Islamic educations amidst increasingly complex digital transformations. This research employs a qualitative approach utilizing a literature review method. Data were gathered from various primary and secondary sources concerning Islamic educational philosophy, fitrah, prophetic ethics, digital literacy, and maqasid sharia (the objectives of Islamic law).The data were analyzed through stages of data reduction, classification, interpretation, and conceptual synthesis. Research findings indicate that the concept of fitrah remains relevant as an ontological foundation for Islamic education; however, it requires reconstruction to align with the characteristics of contemporary digital society. The study also reveals that ethics needs to be reconstructed into a "prophetic digital ethics" framework to address the various ethical challenges arising in the digital space. Furthermore, the integration of digital literacy and maqasid sharia offers a new paradigm for the development of contemporary Islamic education.This research proposes three conceptual constructs digital fitrah, prophetic digital ethics, and maqasid sharia based digital literacy as theoretical contributions to the advancement of Islamic educational philosophy in the digital era. These findings underscore the importance of integrating spirituality, character building, and digital literacy to cultivate individuals who are faithful, morally responsible, critical, and socially collaborative in their use of technology.